Non-Ideal Hall MHD Rayleigh–Taylor Instability in Plasma Induced by Nanosecond and Intense Femtosecond Laser Pulses - Roman S. Zemskov; Maxim V. Barkov; Evgeniy S. Blinov; Konstantin F. Burdonov; Vladislav N. Ginzburg; Anton A. Kochetkov; Aleksandr V. Kotov; Alexey A. Kuzmin; Sergey E. Perevalov; Il’ya A. Shaikin; Sergey E. Stukachev; Ivan V. Yakovlev; et al. (Plasma, 2025)
A pioneering detailed comparative study of the dynamics of plasma flows generated by high-power nanosecond and high-intensity femtosecond laser pulses with similar fluences of up to <semantics>3×104</semantics> J/cm2 is presented. The experiments were conducted on the petawatt laser facility PEARL using two types of high-power laser radiation: femtosecond pulses with energy exceeding 10 J and a duration less than 60 fs, and nanosecond pulses with energy exceeding 10 J and a duration on the order of 1 ns. In the experiments, high-velocity (>100 km/s) flows of «femtosecond» (created by femtosecond laser pulses) and «nanosecond» plasmas propagated in a vacuum across a uniform magnetic field with a strength over 14 T. A significant difference in the dynamics of «femtosecond» and «nanosecond» plasma flows was observed: (i) The «femtosecond» plasma initially propagated in a vacuum (no B-field) as a collimated flow, while the «nanosecond» flow diverged. (ii) The «nanosecond» plasma interacting with external magnetic field formed a quasi-spherical cavity with Rayleigh–Taylor instability flutes. In the case of «femtosecond» plasma, such flutes were not observed, and the flow was immediately redirected into a narrow plasma sheet (or «tongue») propagating across the magnetic field at an approximately constant velocity. (iii) Elongated «nanosecond» and «femtosecond» plasma slabs interacting with a transverse magnetic field broke up into Rayleigh–Taylor «tongues». (iv) The ends of these «tongues» in the femtosecond case twisted into vortex structures aligned with the ion motion in the external magnetic field, whereas the «tongues» in the nanosecond case were randomly oriented. It was suggested that the twisting of femtosecond «tongues» is related to Hall effects. The experimental results are complemented by and consistent with numerical 3D magnetohydrodynamic simulations. The potential applications of these findings for astrophysical objects, such as short bursts in active galactic nuclei, are discussed.